Idiopathic Generalized Epilepsy and Hypokalemic Periodic Paralysis in a Family of South Indian Descent. (26th March 2015) - Subramanian, Muthiah; Senthil, N.; Sujatha, S.
Abstract : Inherited channelopathies are a heterogeneous group of disorders resulting from dysfunction of ion channels in cellular membranes. They may manifest as diseases affecting skeletal muscle contraction, the conduction system of the heart, nervous system function, and vision syndromes. We describe a family of South Indian descent with hypokalemic periodic paralysis in which four members also have idiopathic generalized epilepsy. Hypokalemic periodic paralysis is a genetically heterogeneous channelopathy that has been linked to mutations in genes encoding three ion channels CACNIAS, SCN4A, and KCNJ2 predominantly. Although data on specific gene in idiopathic generalized epilepsy is relatively scarce, mutations of voltage gated sodium channel subunit genes (CACNB4) and nonsense mutations in voltage gated calcium channels (CACNA1A) have been linked to idiopathic generalized epilepsy in two families. We speculate that gene mutations altering the ability of the beta subunit to interact with the alpha subunit of the CaV1.1 channel and mutations in the pore-forming potassium channel subunit may be possible explanations for the combined manifestation of both diseases. Functional analysis of voltage gated calcium channel and other ion channels mutations may provide additional support and insight for the causal role of these mutations. The understanding of mutations in ion-channel genes will lead to improved diagnosis and treatment of such inherited channelopathies.